2019
DOI: 10.1186/s12939-019-1045-8
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver-perceived racial discrimination is associated with diverse mental health outcomes in Aboriginal and Torres Strait Islander children aged 7–12 years

Abstract: Background Racial discrimination is acknowledged as a central social determinant of Australian Aboriginal and Torres Strait Islander (hereafter referred to as Aboriginal) health, although quantitative empirical literature on the impacts of racism on Aboriginal children remains sparse. We use a novel, longitudinal dataset to explore the relationship between caregiver-perceived racism exposure and a range of mental health and related behavioural and physiological outcomes in childhood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 64 publications
1
40
0
Order By: Relevance
“…In Australian Aboriginal and Torres Strait Islander (hereafter referred to as 'Aboriginal') populations, where the pervasiveness of racial discrimination is well documented across legal, healthcare, educational and employment settings, [8][9][10] assessing the link between the psychosocial stressor of racism and physical health remains a challenge. To date, indicators of physical health most commonly comprise self-or carer-rated general health status, with few significant associations found [11][12][13][14][15][16]. Self-reported general health can be a misleading indicator of physical health, particularly for socially disadvantaged populations who may underreport or understate adverse health outcomes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In Australian Aboriginal and Torres Strait Islander (hereafter referred to as 'Aboriginal') populations, where the pervasiveness of racial discrimination is well documented across legal, healthcare, educational and employment settings, [8][9][10] assessing the link between the psychosocial stressor of racism and physical health remains a challenge. To date, indicators of physical health most commonly comprise self-or carer-rated general health status, with few significant associations found [11][12][13][14][15][16]. Self-reported general health can be a misleading indicator of physical health, particularly for socially disadvantaged populations who may underreport or understate adverse health outcomes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the international evidence, primary studies performed in Australia have found positive associations between racism and negative mental health effects on Aboriginal and Torres Strait Islanders [26][27][28]. The negative association with physical health has also been documented [16,29]. However, in Australia, there is scarce of systematic overview on the impact of racism and discrimination on physical and mental health outcomes among Aboriginal and Torres Strait Islander peoples.…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, a study from the state of Victoria found that 17% of Aboriginal and Torres Strait Islander adults had experienced at least one episode of racism in the last year compared with 4.5% of their nonindigenous counterparts [15]. A study conducted among young Aboriginal and Torres Strait Islander children showed a high prevalence of perceived racism from either adults or peers [16].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the international evidence, primary studies performed in Australia have found positive associations between racism and negative mental health effects on Aboriginal and Torres Strait Islanders [27][28][29]. The negative association with physical health has also been documented [17,30].…”
Section: Introductionmentioning
confidence: 86%
“…Moreover, a study from the state of Victoria found that 17% of Aboriginal and Torres Strait Islander adults had experienced at least one episode of racism in the last year compared with 4.5% of their non-Indigenous counterparts [16]. A study conducted among young Aboriginal and Torres Strait Islander children showed a high prevalence of perceived racism from either adults or peers [17].…”
Section: Introductionmentioning
confidence: 99%